The Role and Integration of Social Media with Online Media Practices in Malang to Enhance News Distribution and Audience Engagement - Qorib, Fathul; Najih, Aizun; Saudah; Nurdiarti, Rosalia Prismarini (KOMUNIKATIF : Jurnal Ilmiah Komunikasi, 2025)
This study examines the role of social media in shaping online media practices in Malang, focusing on Jatim Times and Tugu Media Group. This study aims to see how both media use platforms such as TikTok, Instagram, Facebook, and Twitter to spread news, engage with audiences, promote content, and attract advertising. This study uses a qualitative approach, collecting data through in-depth interviews with social media managers, journalists, and editors and analyzing the content on their social media. By comparing interviews, content, and activities on social media, this study provides an overview of how social media influences their strategies. The results show that social media is essential in expanding audience reach, strengthening media identity, and increasing advertising revenue. However, the challenge is how the media balances these promotional efforts while maintaining the credibility of the information that is the primary basis of the media. The benefits of this study are that it will provide a deep understanding for media practitioners and researchers about integrating social media into local media strategies, as well as the challenges faced in maintaining credibility in the digital world. Further research is recommended to focus on the ethical challenges of using social media for news dissemination in Indonesia. ABSTRAK Penelitian ini mengkaji peran media sosial dalam membentuk praktik media online di Malang, dengan fokus pada Jatim Times dan Tugu Media Group. Tujuan penelitian ini adalah untuk melihat bagaimana kedua media tersebut menggunakan platform seperti TikTok, Instagram, Facebook, dan Twitter untuk menyebarkan berita, berinteraksi dengan audiens, mempromosikan konten, serta menarik iklan. Penelitian ini menggunakan pendekatan kualitatif, dengan mengumpulkan data melalui wawancara mendalam dengan manajer media sosial, jurnalis, dan editor, serta menganalisis konten yang ada di media sosial mereka. Dengan membandingkan wawancara, konten, dan aktivitas di media sosial, penelitian ini memberikan gambaran tentang bagaimana media sosial mempengaruhi strategi mereka. Hasil penelitian menunjukkan bahwa media sosial memiliki peran penting dalam memperluas jangkauan audiens, memperkuat identitas media, dan meningkatkan pendapatan dari iklan. Namun, tantangannya adalah bagaimana media menyeimbangkan upaya promosi tersebut dengan tetap menjaga kredibilitas informasi yang menjadi basis utama media. Manfaat dari penelitian ini adalah memberikan pemahaman mendalam bagi praktisi media dan peneliti tentang integrasi media sosial dalam strategi media lokal, serta tantangan yang dihadapi dalam menjaga kredibilitas dalam dunia digital. Penelitian selanjutnya disarankan untuk lebih fokus pada tantangan etis dalam penggunaan media sosial untuk penyebaran berita di Indonesia.